Dampak Kenaikan Harga Pupuk terhadap Penggunaannya pada Usahatani Cabai Keriting di Kota Pekanbaru - Siti Nurhaliza Amrin; Syaiful Hadi; Cepriadi Cepriadi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The cost of fertilizer has increased is one of the problems complaints made by farmers in cultivating curly chilies in Pekanbaru City. Therefore, this research aims to analyze the impact of increasing fertilizer prices on their use in curly chili farming. This research was conducted on curly chili farming in 9 sub-districts in Pekanbaru City using a survey approach and purposive sampling technique with the criteria of curly chili farmers farming both before and after the price rise for fertilizer, totaling 30 respondent farmers. Data were analyzed using quantitative descriptive methods using the data processing software SPSS version 25. The study's findings demonstrate how fertilizer use changed in Pekanbaru City's output of curly chilies both before and after fertilizer costs rose. The amount of manure used likewise halted at 10,000 kg/ha/mt, while the amount of NPK fertilizer used decreased from 12,000 kg/ha/mt to 10,000 kg/ha/mt. 200 kg/ha/mt as opposed to the prior 300 kg/ha/mt.